Developmental tasks of terminally ill patients - Andrews, Paul (Journal of religion and health, 1981)
Erikson's epigenetic stages provide a conceptual map of how a person responds to the knowledge of having a terminal illness. The patient initially reworks developmental tasks that have been resolved and then works at an accelerated pace to accomplish tasks that remain ahead. This acceleration is an attempt to attain a wholeness of self and life in light of the threat of imminent death and self-perceived shortened life span.